Utilisation and Willingness to pay for MCH Services in Bangladesh : An Evidence from Urban Primary Health Care - Sharmin, Mizan (Universiti Malaysia Sarawak (UNIMAS), 2020)
Introduction: Bangladesh has experienced rapid urbanisation in recent decades. Both urbanisation and poverty with health and survival of human being. This study was aimed to investigate the factors affecting the utilisation of MCH care services through Urban Primary Health Care Project Clinic (UPHCPC) in Bangladesh and to determine the quality of life and satisfaction of MCH care services. The study was also aimed to ascertain the willingness to pay (WTP) for MCH services and factors thereof. Materials and Methods: This cross-sectional study was conducted in 10 city corporation and four selected municipalities in Bangladesh. A two-stage cluster sampling was done to select the ever-married women aged 15-49 years in the catchment areas of UPHCP in Bangladesh. Data were collected from 3949 women having at least one child aged two years and below. Data were collected through face to face interview, using a pre-tested and validated questionnaire. IBM SPSS version 22.0 was used for quantitative data analysis. Results: The overall utilisation of maternal and child health care was found to be satisfactory. The multinomial logistic regression analysis revealed that the usage of MCH services from UPHCP clinic was associated with division, age, having an entitlement card, wealth index, family income and expenditure, ownership status in the non-poor and poor catchment areas. Urban women had an average level of quality of life. However, it was higher among the women from the non-poor than the poor catchment area. The multiple linear regression analysis found out that possessing an entitlement card, income and the utilisation of MCH services were significantly related to the quality of life. Most of the respondents were willing to pay (WTP) for health insurance, user fees and medicine. Most of them wanted to pay BDT 10-20 (USD 0.24) for HI, 51-100 (USD 1.19) for medicine and BDT 5-10 (USD 0.12) for user fees. The analysis with generalised linear modelling with log link function identified the age, level of education, wealth index, ownership status, utilisation of urban primary health care clinic, quality of life as the potential predictors of the different scenario of WTP. Conclusion: The study revealed that WTP was influenced by the quality of life and utilisation of MCH services. Targeting poor section of UPHCP is an effective way to provide primary health care services including MCH services in urban areas to improve the usage of services. This could be ensured through the distribution of Entitlement Card. The utilisation of MCH services was positively correlated with QOL of the poor. To improve service utilisation for the marginalised urban poor, steps like the sustainable primary health care program including MCH services with universal health coverage and supported by health insurance and providing of entitlement card with minimum registration fees are required.